Characterisation of deuterium distributions in corroded zirconium alloys using high-resolution SIMS imaging. (November 2020) - Liu, Junliang; Li, Kexue; Sayers, James; Aarholt, Thomas; He, Guanze; Hulme, Helen; Garner, Alistair; Preuss, Michael; Nordin, Heidi; Partezana, Jonna M.; Limbäck, Magnus; Lozano-Perez, Sergio; et al.
Abstract: Hydrogen diffusion through the oxide grown on Zr alloys by aqueous corrosion processes plays a critical role in determining the rate of hydrogen pickup (HPU) which can result in embrittlement of fuel cladding and limit the burnup of the nuclear fuel it encapsulates. Mapping the hydrogen/deuterium distributions in these oxide layers, especially in the barrier layer close to the metal/oxide interface, is a powerful way to understand the mechanism of both oxidation and hydrogen pickup. Here we have characterised by high-resolution SIMS analysis the deuterium distribution in oxide layers on a series of Zr alloys, including autoclave-oxidised Zircaloy-4, Zr-1Nb and Zr-2.5Nb alloys, and in-flux and out-of-flux corroded Zr-2.5Nb samples. Pre-transition Zircaloy-4 samples show a high deuterium trapping ratio in the oxide and a higher diffusion coefficient than in oxides on the Nb-containing samples. Neutron irradiation increases the deuterium diffusion coefficient, the deuterium concentration in the oxide and the pickup fraction in Zr-2.5 Nb samples. Comparative NanoSIMS and EDX/SEM analysis demonstrates that the deuterium is not preferentially trapped at second phase particles in the oxides on any of the alloys studied, but there is direct evidence for trapping at the surfaces of small oxide cracks especially in Zircaloy-4 samples. The high resolution mapping of these hot-spots in 3D can provide unique information on the mechanisms of hydrogen uptake, and suggests that the development of interconnected porosity in the oxide may be the critical rate-determining mechanism that controls HPU in the aqueous corrosion of zirconium alloys in water-cooled reactors. Graphical abstract: Image, graphical abstract